2010
DOI: 10.1007/s10198-010-0281-z
|View full text |Cite
|
Sign up to set email alerts
|

Health care costs and their predictors of inflammatory bowel diseases in Germany

Abstract: This is the first study to calculate costs due to CD and UC from the perspective of the SHI in Germany and to identify cost-driving factors. It confirms a high economic burden of IBD to payers and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
(33 reference statements)
1
24
1
1
Order By: Relevance
“…Although there is evidence that Crohn's disease generates more health care use than ulcerative colitis [5,7,22], no such differences were found in our study. The IBD patients reported significantly more often that they had visited a physician during the previous year due to gastrointestinal reasons than did patients with IBS.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Although there is evidence that Crohn's disease generates more health care use than ulcerative colitis [5,7,22], no such differences were found in our study. The IBD patients reported significantly more often that they had visited a physician during the previous year due to gastrointestinal reasons than did patients with IBS.…”
Section: Discussioncontrasting
confidence: 83%
“…Studies from North America and some European countries have shown that IBD patients use more health services when compared with the background population [10][11][12]. IBDs being fluctuating in severity, a minority of the patients incur the majority of the costs [7,13,14]. There is some indication that IBD also affects work productivity; IBD has adverse effects on the whole employment career [11] and social functions such as housework and hobbies [13].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…35 It has been reported that the top 10% of patients with highest charges account for 50% of the total cost of IBD care. 6 Therefore, it is important to identify these high-risk patients and intervene to best prevent complications and improve quality of life.…”
mentioning
confidence: 99%
“…Ein erhöhtes Risiko für Komplikationen der immunsuppressiven Therapie besteht insbesondere bei langdauernder Steroideinnahme, bei älteren Patienten und bei kombinierter Immunsuppression [242,244,394,395]. Inwieweit Medikamentenkosten, die bei den Anti-TNF-α-Antikörpern deutlich höher als bei Azathioprin liegen, einen wesentlichen Einfluss auf die Therapieentscheidung haben sollten, ist zu diskutieren [396]. Darüber hinaus gibt es Daten, dass bei bestimmungsgemäßem Gebrauch der Einsatz von Anti-TNF-α-Antikör-pern kosteneffizient sein kann [397].…”
Section: Kinder Und Jugendlicheunclassified